“EducaBlog”: contribution to social education from the professional profile - Rodríguez Torre, Iñigo; Dosil Santamaría, Maria; Gezuraga Amundarain, Monike; Darretxe Urrutxi, Leire (Revista Colombiana de Ciencias Sociales, 2024)
This research is part of a larger study and aims to analyze the case of EducaBlog, a professional blog of social education, from a phenomenological perspective to analyze its contribution to the professionalization, identity, and professional development of social education. This report presents the quantitative results and compares them with qualitative ones, both collected through a virtual questionnaire that was aimed at professionals from the third social sector who follow EducaBlog. The analysis was performed using SPSS V.26 software (INC., Chicago, IL) for quantitative data and NVIVO 12 V. Release 1.5 for qualitative data. The results showed that EducaBlog users identify it as a professional learning space that contributes both to professionalization, to identity and to professional development.